IFT27 Links the BBSome to IFT for Maintenance of the Ciliary Signaling Compartment - Eguether, Thibaut; San Agustin, Jovenal T.; Keady, Brian T.; Jonassen, Julie A.; Liang, Yinwen; Francis, Richard; Tobita, Kimimasa; Johnson, Colin A.; Abdelhamed, Zakia A.; Lo, Cecilia W.; Pazour, Gregory J. (Developmental cell, 2014)
Vertebrate hedgehog signaling is coordinated by the differential localization of the receptors patched-1 and Smoothened in the primary cilium. Cilia assembly is mediated by intraflagellar transport (IFT), and cilia defects disrupt hedgehog signaling, causing many structural birth defects. We generated Ift25 and Ift27 knockout mice and show that they have structural birth defects indicative of hedgehog signaling dysfunction. Surprisingly, ciliary assembly is not affected, but abnormal hedgehog signaling is observed in conjunction with ciliary accumulation of patched-1 and Smoothened. Similarly, Smoothened accumulates in cilia on cells mutated for BBSome components or the BBS binding protein/regulator Lztfl1. Interestingly, the BBSome and Lztfl1 accumulate to high levels in Ift27 mutant cilia. Because Lztfl1 mutant cells accumulate BBSome but not IFT27, it is likely that Lztfl1 functions downstream of IFT27 to couple the BBSome to the IFT particle for coordinated removal of patched-1 and Smoothened from cilia during hedgehog signaling. •IFT27 is not required for cilia assembly but is required for hedgehog signaling•Ift27 mutant cells accumulate Lztfl1, the BBSome, and hedgehog receptors in cilia•Lztfl1 bridges IFT27 to the BBSome in the removal of hedgehog receptors from cilia In vertebrates, hedgehog signaling is organized in the cilium, and ciliary defects affect signaling. Eguether et al. find that intraflagellar transport proteins IFT25 and IFT27 are not required for ciliary assembly but couple ciliary trafficking of hedgehog signaling components to the IFT particle through the BBSome and BBSome regulator Lztfl1.